(untitled) (Journal of Preventive and Social Medicine, 2025)
Background: Tea, derived from the Camellia sinensis plant, is a globally consumed beverage with a rich history. Despite its widespread production, smaller gardens produce unique teas highly valued by enthusiasts. The tea industry in Bangladesh, particularly in Sylhet, plays a pivotal role in the economy but is plagued by challenges such as work-related health issues among its predominantly marginalized and tribal labor force. This study aimed to explore the health and lifestyle challenges faced by tea workers in Sylhet. Methods: A cross-sectional study was conducted in three tea gardens in Sylhet, focusing on socio-demographic characteristics, work-related health problems, and healthcare-seeking behaviors. Data were collected from 255 participants using a semi-structured questionnaire, and statistical analyses, including Chi-Square test, were performed using SPSS version 26. Results: The socio-economic profile revealed a predominantly female, Hindu, and illiterate workforce with low income. Musculoskeletal disorders (MSDs) were prevalent, affecting 77.6% of participants, with lower back pain being the most common. Common diseases, injuries, and respiratory issues were reported. Allopathic treatment was preferred by 78% of respondents. Significant associations were found between MSDs and age, education, smoking, and drug use. Job-related factors like nature of work and weekly working hours also showed significant associations (p<0.05). Conclusion: The study highlights the multifaceted challenges faced by tea garden workers, emphasizing the need for targeted interventions considering socio-demographic and occupational factors. Insights from this research can inform policies and healthcare strategies to improve the well-being of this vulnerable population. Further research and collaborative efforts are warranted to address the complexities of the tea industry and promote the health and rights of its workforce. JOPSOM 2023; 42(2): 36-42